A Randomized Trial to Assess Effectiveness and Safety of a Hyaluronic Acid Filler for Chin Augmentation and Correction of Chin Retrusion. Issue 6 (20th September 2022) - Marcus, Keith; Moradi, Amir; Kaufman-Janette, Joely; Ablon, Glynis; Donofrio, Lisa; Chapas, Anne; Kazin, Rebecca; Rivkin, Alexander; Rohrich, Rod J.; Weiss, Robert; George, Rosalyn
Abstract : Background: The chin is important for facial appearance, affecting overall balance and harmony of the face. The purpose of this study was to evaluate effectiveness of the hyaluronic acid filler Restylane Defyne for chin augmentation and correction of chin retrusion versus a no-treatment control. Methods: Male and female subjects, aged 22 years or older, with mild to moderate chin retrusion, were randomized 3:1 to the hyaluronic acid filler Restylane Defyne ( n = 107) or no treatment ( n = 33). Assessments included live, blinded evaluations on a validated chin retrusion scale (Galderma Chin Retrusion Scale), aesthetic improvement (Global Aesthetic Improvement Scale), subject-reported FACE-Q Satisfaction with Chin, and safety follow-up. Results: Galderma Chin Retrusion Scale responder rate (≥1 grade improvement) was higher for the hyaluronic acid filler Restylane Defyne (81 percent) than for control (6 percent) ( p < 0.001) at week 12, and remained higher at week 48 (74 percent versus 11 percent; p < 0.001). Aesthetic improvement rates were high throughout the study as reported by investigators (≥96 percent) and subjects (≥85 percent). Subject satisfaction was higher in the hyaluronic acid filler Restylane Defyne group than in the control group at week 12 ( p < 0.001). In the individual FACE-Q scale items, 87 to 98 percent of subjects were satisfied at week 12. Treatment-related adverse events were mild to moderate. Conclusions: The hyaluronic acid filler Restylane Defyne was safe and effective for augmentation of the chin region to improve the chin profile and associated with high aesthetic improvement and subject satisfaction. Effectiveness was sustained throughout 48 weeks. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.